ONE-YEAR EVALUATION OF OVERALL URETHRAL STRICTURE MANAGEMENT USING QUESTIONNAIRES AND UROFLOWMETRY - Mediana, Ervita; Wahyudi, Irfan; Rodjani, Arry (Indonesian Journal of Urology, 2014)
Objective: To evaluate the overall outcomes of patients who get definitive treatment of urethral stricture. Material & Method: All patients who underwent various urethral stricture management in Cipto Mangunkusumo Hospital were evaluated over 1 year period. Patient demographics, type of surgery, International Prostate Symptoms Score (IPSS), quality of life (QoL) score, flow rate (FR) and post void residual urine (PVR) of all patients were evaluated at 3 months, 6 months and 1 year after surgery. Results: Out of 230 urethral stricture patients, 65 patients were eligible this study. Mean patient age was 41.19 ± 20.44 years. 37Direct Vision Internal Urethrotomy (DVIU), 20 end-to-end anastomosis, and 8 graft urethroplasties were performed. All patients underwent urethral stricture management showed improvement of IPSS (-22.64, p < 0.001), QoL (-3.36, p < 0.001), FR (16.72 ml/s, p < 0.001) and PVR (-126.23 ml, p < 0.001). Compliant patients showed better improvement of IPSS and FR than non compliant patient after DVIU procedure. Overall, open surgery give better improvement of IPSS and FR than DVIU procedure. These differences were more pronounced in recurrent and long (≥ 2 cm) urethral stricture disease. In open surgery group, end-to-end anastomosis give better improvement in FR compared to graft urethroplasty. Conclusion: Patients undergoing urethral stricture management experienced a significant improvement in self-reported outcomes and functional uroflow studies. Overall, open surgery gives better improvement in FR and IPSS than DVIU procedure. In open surgery group, end-to-end anastomosis give better improvement compares to graft urethroplasty.Keywords: International Prostate Symptoms Score, quality of life, flow rate, post void residual urine, urethral stricture.